2009
DOI: 10.1097/mcg.0b013e3181919a33
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Hepatic Phenotype Between Hemochromatosis Patients With HFE C282Y Homozygosity and Other HFE Genotypes

Abstract: Objective-There are limited data comparing hepatic phenotype among hemochromatosis patients with different HFE genotypes. The goal of this study was to compare hepatic histopathologic features and hepatic iron concentration (HIC) among patients with phenotypic hemochromatosis and different HFE genotypes.Methods-We studied 182 U.S. patients with phenotypic hemochromatosis. Degree of hepatic fibrosis, pattern of iron deposition, presence of steatosis or necroinflammation, and HIC were compared among different HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 15 publications
0
26
1
Order By: Relevance
“…It is well-known that the liver IO in HH produced by the C282Y/C282Y mutation is higher than that produced by other mutations, such as C282Y/H63D or H63D/H63D (6,15). The causative role of C282Y/H63D and H63D/H63D mutations in HH or IO has been demonstrated, but with less penetrance and a considerable phenotypic variability (6,15). The absence of C282Y homozygotic patients in our study may have been why no differences were detected.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…It is well-known that the liver IO in HH produced by the C282Y/C282Y mutation is higher than that produced by other mutations, such as C282Y/H63D or H63D/H63D (6,15). The causative role of C282Y/H63D and H63D/H63D mutations in HH or IO has been demonstrated, but with less penetrance and a considerable phenotypic variability (6,15). The absence of C282Y homozygotic patients in our study may have been why no differences were detected.…”
Section: Discussioncontrasting
confidence: 45%
“…One of the problems in this study is that there were no C282Y/C282Y patients in the series. It is well-known that the liver IO in HH produced by the C282Y/C282Y mutation is higher than that produced by other mutations, such as C282Y/H63D or H63D/H63D (6,15). The causative role of C282Y/H63D and H63D/H63D mutations in HH or IO has been demonstrated, but with less penetrance and a considerable phenotypic variability (6,15).…”
Section: Discussionmentioning
confidence: 99%
“…2,104 High ferritin levels have also been found to be closely associated with the development of hepatic fibrosis in Cys282Tyr homozygous or Cys282Tyr/His63Asp heterozygous patients of advanced age. 118 Conclusions A diagnosis of hereditary hemochromatosis can easily be based on the characteristically raised concentrations of circulating markers of iron metabolism in the blood, followed by genetic testing and, if confirmed, by screen ing of firstdegree relatives. [1][2][3][4] Early initiation of therapy can avoid tissue damage and organ failure as a conse quence of progressive iron accumulation.…”
Section: Infections and Inflammationmentioning
confidence: 99%
“…Large population studies have shown that both the compound heterozygous and homozygous H63D genotypes have much lower penetrance than the C282Y homozygous genotype (1,2). In the haemochromatosis phenotype, hyper-ferritinaemia, transferrin saturation (1,5) and increased hepatic iron concentration (6) are associated with H63D homo-or hetero-zygosity as observed with C282Y homozygotes or C282/H63D.…”
mentioning
confidence: 92%